작업치료과 대학생의 직업기초능력, 구직효능감 및 진로준비행동의 관계 - 박주영; 김훈주; Park, Juyoung; Kim, Hunju (Journal of the Korean Society of Integrative Medicine, 2019)
Purpose : The purpose of this study was to understand the correlations between occupational basic competencies, job searching efficacy and career preparation behavior of department on occupational therapy students. Methods : The subjects of this study were 103 occupational therapy students in D college. The data collection period was from July 1, 2018 to July 30, 2018. The collected data was processed using SPSS 21.0 and were analyzed using descriptive statistics, t-test, ANOVA, Scheffe's test and Pearson's correlation coefficient. Results : The mean scores for occupational basic competencies, job searching efficacy and career preparation behavior of the occupational therapy students were 3.61 (${±}0.59$), 3.58 (${±}0.61$) and 3.31 (${±}0.66$) respectively. The occupational basic competencies score of the Occupational Therapy students was significantly differed according to their age (t=-2.13, p=.03) and grade point average (F=15.01, p=.00). The job searching efficacy of the Occupational Therapy students was significantly different by grade point average (F=3.40, p=.02). There were no significant differences in job preparation behaviors among occupational therapy students according to gender, age, grade and grade point average. There was a positive correlation between occupational basic competencies and job searching efficacy (r=.675, p<.01), between occupational basic competencies and career preparation behavior (r=.455, p<.01), between job searching efficacy and career preparation behavior (r=.702, p<.01). Conclusion : The results of this study suggest the following: It is necessary to repeat this study with a greater number and range of subjects. In addition, it suggests that the progress of study should be developed and continued and refined in order to identify factors that affect the career preparation behavior of students of occupational therapy. In addition, the development of a program and the application of a curriculum to promote occupational basic competencies and job searching efficacy should be a priority.